Genomic determinants of triglyceride and cholesterol distribution into lipoprotein fractions in the rat - Hodúlová, Miloslava; Šedová, Lucie; Křenová, Drahomíra; Liška, František; Krupková, Michaela; Kazdová, Ludmila; Tremblay, Johanne; Hamet, Pavel; Křen, Vladimír; Šeda, Ondřej (PloS one, 2014)
The plasma profile of major lipoprotein classes and its subdivision into particular fractions plays a crucial role in the pathogenesis of atherosclerosis and is a major predictor of coronary artery disease. Our aim was to identify genomic determinants of triglyceride and cholesterol distribution into lipoprotein fractions and lipoprotein particle sizes in the recombinant inbred rat set PXO, in which alleles of two rat models of the metabolic syndrome (SHR and PD inbred strains) segregate together with those from Brown Norway rat strain. Adult male rats of 15 PXO strains (n = 8-13/strain) and two progenitor strains SHR-Lx (n = 13) and BXH2/Cub (n = 18) were subjected to one-week of high-sucrose diet feeding. We performed association analyses of triglyceride (TG) and cholesterol (C) concentrations in 20 lipoprotein fractions and the size of major classes of lipoprotein particles utilizing 704 polymorphic microsatellite markers, the genome-wide significance was validated by 2,000 permutations per trait. Subsequent in silico focusing of the identified quantitative trait loci was completed using a map of over 20,000 single nucleotide polymorphisms. In most of the phenotypes we identified substantial gradient among the strains (e.g. VLDL-TG from 5.6 to 66.7 mg/dl). We have identified 14 loci (encompassing 1 to 65 genes) on rat chromosomes 3, 4, 7, 8, 11 and 12 showing suggestive or significant association to one or more of the studied traits. PXO strains carrying the SHR allele displayed significantly higher values of the linked traits except for LDL-TG and adiposity index. Cholesterol concentrations in large, medium and very small LDL particles were significantly associated to a haplotype block spanning part of a single gene, low density lipoprotein receptor-related protein 1B (Lrp1b). Using genome-wide association we have identified new genetic determinants of triglyceride and cholesterol distribution into lipoprotein fractions in the recombinant inbred panel of rat model strains.
Keywords: Animals; cholesterol; Genome-Wide Association Study; jednonukleotidový polymorfismus; lipoproteiny; triglyceridy; druhová specificita; Genomics; Triglycerides; Polymorphism, Single Nucleotide; Species Specificity; Cholesterol; Male; celogenomová asociační studie; krysa rodu Rattus; Lipoproteins; zvířata; mužské pohlaví; Rats; genomika